Etanercept in the treatment of rheumatoid arthritis. (October 2013) - Hunt, Laura; Emery, Paul
Abstract : Introduction: Biologic agents have transformed clinical outcomes in rheumatoid arthritis, and there are now several immune-modulating therapies available. Tumour necrosis factor-α (TNF-α) inhibitors were the first biologic drug class licensed for the treatment of rheumatoid arthritis.Etanercept is a fusion protein composed of two TNF receptors bound to the constant portion (Fc) of human immunoglobulin G (IgG). Areas covered: This article will consider the pharmacological properties of etanercept and the clinical efficacy data presented in clinical trials. Its safety in clinical practice will be reviewed. Expert opinion: There is overwhelming evidence to support the use of etanercept in rheumatoid arthritis. Trial data demonstrate etanercept's efficacy in reducing structural damage, improving clinical outcomes and inducing remission. Optimal response to therapy is seen when used in combination with methotrexate and when initiated early. Etanercept is an attractive therapeutic option given the excellent safety profile, reduced immunogenicity and ease of administration.